Innovation in Indonesian Language Learning: The Impact of Flipbook Media on Elementary School Students’ Learning Outcomes - Azizah, Evi Dwi; Sukardi (Jurnal Ilmiah Sekolah Dasar, 2024)
The "5W + 1H" aspect (what, where, when, who, why, how) is the subject matter studied by fifth-grade elementary school students. Lack of language literacy, student enthusiasm, and inadequate use of learning media are problems for class V students in understanding the material. This research aims to analyze the influence of flipbook media on the learning outcomes of Indonesian language material "5W+1H" for fifth-grade elementary school students. This quantitative research uses a quasi-experimental design of a pre-test, post-test, and non-equivalent control group design. The population in this study was 125 fifth-grade elementary school students. The sample for this research was 26 fifth-grade elementary school students. Data collection methods use tests and questionnaires. Data collection instruments include questionnaires and test questions. Data analysis for this research used the SPSS 16 application in the form of a normality test, homogeneity test, t-test, N-Gain test, and average percentage of student responses. The research results showed a difference in the average post-test scores for the experimental class and the control class students. The average Indonesian language learning results for the experimental class using flipbook media were better than the average Indonesian language learning results for the control class. It was concluded that Flipbook Media helps students learn, increases enthusiasm for learning, and influences Indonesian language learning outcomes in the "5W+1H" material.